Clinicopathological features of uterine fibroid in a tertiary care teaching hospital - Singh, Priyanka; Mirza, Sadaf; Trivedi, Pawan; Singh, Tanya (International Journal of Research in Medical Sciences, 2021)
Background: Uterine fibroids are one of the common benign tumours of uterus seen in women of reproductive age group. These constitute 5-10% of all these tumours. Methods: Total of 56 patients above 21 years of age reporting to OPD or emergency of gynaecology department of the Mayo Institute and found to be suffering from leiomyoma of the uterus were included in the study. Results: Clinical manifestations seen in cases with uterine fibroid. Menstrual irregularities were seen in 69.64% of cases. 39.28% suffered from abdominal pain and infertility was seen in 10.71% cases. Endometrial changes during the histopathological examination. In 71.42% of cases, proliferative endometrium was found. Secretory endometrium was seen in 14.28% and atrophic in 8.92%. Conclusions: Leiomyoma is the most well-known uterine tumor seen in gynecological practice. Feminine aggravations are the commonest manifestation of which menorrhagia is the most well-known show. The vast majority of these tumors are intramural in area. The most widely recognized example of endometrium noticed is proliferative. Hyaline degeneration, myxoid degeneration and cystic degeneration are the normal auxiliary changes found in fibroid uterus.